Inferior parietal lobule encodes visual temporal resolution processes contributing to the critical flicker frequency threshold in humans. - Andrea Nardella (Public Library of Science (PLoS), 2014)
The measurement of the Critical Flicker Frequency threshold is used to study the visual temporal resolution in healthy subjects and in pathological conditions. To better understand the role played by different cortical areas in the Critical Flicker Frequency threshold perception we used continuous Theta Burst Stimulation (cTBS), an inhibitory plasticity-inducing protocol based on repetitive transcranial magnetic stimulation. The Critical Flicker Frequency threshold was measured in twelve healthy subjects before and after cTBS applied over different cortical areas in separate sessions. cTBS over the left inferior parietal lobule altered the Critical Flicker Frequency threshold, whereas cTBS over the left mediotemporal cortex, primary visual cortex and right inferior parietal lobule left the Critical Flicker Frequency threshold unchanged. No statistical difference was found when the red or blue lights were used. Our findings show that left inferior parietal lobule is causally involved in the conscious perception of Critical Flicker Frequency and that Critical Flicker Frequency threshold can be modulated by plasticity-inducing protocols.